Assessment of Proverbs in the Translation Class: Didactic Proposal for University Students - Stîngă, Paula Andreea (2026)
This article addresses a contrastive and didactic approach to working with proverbs in two Romance languages, Spanish and Romanian. Based on a didactic proposal for a translation class with Romanian students from Babeș-Bolyai University, a corpus of 65 paremias, proverbs, and phrases is offered. Through a student translation diary, feedback is collected about the translation process and the evaluation of the proposal. The results allow us to collect a contrastive classification, in addition to highlighting the translatological differences in the two languages, the predominance of proverbs related to ethical and moral values or standards of conduct. Likewise, it evidences the great impact of the didactic proposal on the development of autonomy, communicative, translation and strategic competence.